PENGARUH MODEL PEMBELAJARAN GUIDED DISCOVERY DISERTAI LKS BERBASIS MULTIREPRESENTASI TERHADAP KEMAMPUAN REPRESENTASI VERBAL, DAN GAMBAR (VG) SISWA DALAM PEMBELAJARAN FISIKA DI SMA - Susiana Susiana; I Ketut Mahardika; Rayendra Wahyu Bachtiar (JURNAL PEMBELAJARAN FISIKA, 2017)
The purposes of this study are assessing the effect of guided discovery learning model with LKS based on multirepresentation to the Senior High School student’s ability of physics verbal, images (VG) representations, and describing student learning activities. The type of this research is an experimental research. Population of the research was all student’s at SMA Negeri 1 Tapen Bondowoso. Physics VG representation is collected through test, and student learning activities is collected through observations and portofolio. The test results of experimental class and control class are analysed by independent sample t-test using SPSS version 22. The results of the analysis of independent sample t-test for the ability of verbal representations show the Sig. (One-tailed) was 0.000. The results of the analysis of independent sample t-test for the ability of pictorial representations show the Sig. (One-tailed) was 0.000. It can be concluded that guided discovery learning model based LKS based on multirepresentation significantly affect the SMA Negeri 1 Tapen Bondowoso student’s ability of physics VG. The score of student learning activities during learning process are using guided discovery learning model with LKS based on multirepresentation is 88%, it is included very active category.